EVALUASI PENCATATAN TRANSAKSI SIMPANAN PIHAK KETIGA DALAM KAITANNYA DENGAN PELAPORAN KEUANGAN PT. BANK NUSANTARA PARAHYANGAN - Fauzi, Rizki Ahmad (Jurnal Ilmiah Binaniaga, 2012)
Bank is an institution acting as financial intermediary between those who have money and those who needs funds. The important role of the bank as financial intermediary in concrete action is to collect and to distribute public funds efficiently and effectively.Fund sources of the bank is divided into three categories, namely: the first party funds (from the bank it self), the second party funds (on loan from outside parties), and third party funds (from the public, it is the most important source of funding for operational activities by the bank). The goal of this research is to find out how the operational procedure and transaction recording of the third party funds (savings, time deposits, and demand deposits) such as account bookkeeping, depositing, withdrawal, interest accounting, administration costs, closure, and evaluation of the correlation between transaction recording of the third party funds and finance reporting of PT. Bank Nusantara Parahyangan. The research conducted by the author is on PT. Bank Nusantara Parahyangan Bogor Branch located in Jalan Surya Kencana No. 99, Bogor 16126. PT.Bank Nusantara Parahyangan is a foreign exchange bank and perceptions bank. The result of this research shows that the operational procedure applied by PT. Bank Nusantara Parahyangan Bogor Branch associated with the third party funds can be said as good enough in accordance with Finance Accounting Standard Code (PSAK No.31, Revised: 2000), about banking accounting, just exactly at recognition of interest charge. It is as well in  accordance with Government Regulation on interest tax as high as 20% and it is final to savings balance (savings, time deposits, and demand deposits) above Rp.7.500.000,00. The conclusion is the implementation of the procedure, transactions recording related to the third party funds and finance reporting of PT. Bank Nusantara Parahyangan Bogor Branch is adequate and has followed the guideline in Finance Accounting Standard Code (PSAK No.31, Revised: 2000).Keywords : The Transaction of the Third Party Funds; Finance Reporting